Race on trial : black defendants in Ontario's criminal courts, 1858-1958 - Walker, Barrington, 1970- (Canadian social history series., 2011)
Using capital case files and the assize records for Kent and Essex counties, areas that had significant black populations because they were termini for the Underground Railroad, Barrington Walker investigates the limits of freedom for Ontario's African Canadians. Through court transcripts, depositions, jail records, Judge's Bench Books, newspapers, and government correspondence, Walker identifies trends in charges and convictions in the Black population. This exploration of the complex and often contradictory web of racial attitudes and the values of white legal elites not only exposes how blackness was articulated in Canadian law but also offers a rare glimpse of black life as experienced in Canada's past."--Publisher